Two-Phase Air/Oil Flow in Aero-Engine Bearing Chambers – Assessment of an Analytical Prediction Method for the Internal Wall Heat Transfer - A. Glahn; S. Wittig (International Journal of Rotating Machinery)
The present paper gives a theoretical outline on liquid film flows driven by superimposed effects of interfacial shear and gravity forces and discusses related heat transfer processes which are relevant for lubrication oil systems of aero engines. It is shown that a simple analytical approach is able to predict measured heat transfer data fairly well. Therefore, it offers scope for improvements within the analysis of bearing chamber heat transfer characteristics as well as for appropriate studies with respect to other components of the lubrication oil system such as vent pipeline elements.